Empowering Business Process Improvement of Kue Basah Ny. Anong in Cianjur, West Java - Cynthia Yuni Luis; Winston Purnama; Hans Nicholas; Vincent Jonathan; Arvin Victor Maruli; Abbytha Zweima A.R. Wartono; Albert Hasudungan (Sekolah Tinggi Manajemen IPMI, 2020)
SMEs in Indonesia have given a significant monetary contribution to the Indonesian economy. In our Community Development case study in Cianjur, some of the community members showed enthusiasm in SME business. In this study, the case was observed through Kue Basah Ny. Anong, which was the business’ brand name. In Indonesia itself, the obstacles of SME businesses were inefficient and ineffective business processes to enhance their business growth. These drawbacks were also found in Kue Basah Ny. Anong. These Community Development activities were held to improve their business process on operational, financial, marketing, and human resource aspects. Firstly, in the operational aspect, the activities were to improve food hygiene and standardization. Secondly, in the financial aspect, this Community Development project provided training and facilitation to make daily financial bookkeeping to monitor their business progress. In the marketing aspect, the assistance was to find other alternative marketing strategies to expand marketing through social media and WhatsApp. This tool was considered effective as the consumers in Cianjur possessed mobile phones. In the human resource aspect, training was provided to Mrs. Anong’s family members to promote their business and products to potential business partners and consumers. From the Community Development intervention, the impact was a better business model canvas and approach toward their customers and partners within six months of this Community Development project (one semester). The period of this Community Development project was from January to June 2020.